2018
DOI: 10.1002/gj.3104
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry of the Carboniferous Ulann Tolgoi granite complex from northern Inner Mongolia, China: Petrogenesis and tectonic implications for the Uliastai continental margin

Abstract: This study presents zircon U–Pb ages and geochemical and Sr–Nd isotopic data for acid granites from the Uliastai continental margin, which is located in the Ulaan Tolgoi area of the south‐eastern Central Asian Orogenic Belt (CAOB). Although most samples have similar calc‐alkaline (K2O/Na2O = 0.55–1.70, average of 1.35) and peraluminous (A/CNK = 1.02–1.20 and A/NK = 1.09–1.87) characteristics, the granodiorites, monzogranites, and alkali feldspar granites exhibit distinct light rare earth element (LREE)/heavy R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 119 publications
(196 reference statements)
1
3
0
Order By: Relevance
“…The 1248–1000, 925–840 Ma age populations are similar to the ages of Xilin Gol Complex, Inner Mongolia (Xu et al, 1996; Hao & Xu, 1997; Shi et al, 2003; Zhu et al, 2004). The 1552–1285 Ma age populations are similar to the ages of volcanic rocks in the Yingchengzi Formation in the northern Songliao Basin and granites in the north of North‐eastern China (Gao et al, 2008; Li et al, 2011; Zhang, Chen, et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…The 1248–1000, 925–840 Ma age populations are similar to the ages of Xilin Gol Complex, Inner Mongolia (Xu et al, 1996; Hao & Xu, 1997; Shi et al, 2003; Zhu et al, 2004). The 1552–1285 Ma age populations are similar to the ages of volcanic rocks in the Yingchengzi Formation in the northern Songliao Basin and granites in the north of North‐eastern China (Gao et al, 2008; Li et al, 2011; Zhang, Chen, et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Some studies have demonstrated that IMPU is the origin of pyroclastic rocks in the eastern NCC (Zhang et al, 2007;Wang et al, 2020). The tonstein samples in this study have distinct negative Eu anomalies; however, pyroclastic rocks in the eastern NCC display weak negative Eu anomalies (Zhou et al, 2001(Zhou et al, , 2018Zhao et al, 2019;Wang et al, 2020). In parallel, the tonsteins in the Benxi Formation have no similar negative ε Hf (t) values compared to rocks from the magmatic arc in the IMPU (Fig.…”
Section: Tectonic Implicationsmentioning
confidence: 57%
“…This research also can infer the same conclusion, which also can suggest the distribution area of (Winchester and Floyd, 1977); (c, d) Zr/TiO 2 vs. Al 2 O 3 /TiO 2 and Nb/Yb vs. Al 2 O 3 /TiO 2 diagrams for the tonsteins. Colored fields represent late Carboniferous to early Permian volcanic rocks from the North China craton (Su et al, 2012;Zhao et al, 2017;Liu et al, 2018;Tian et al, 2018;Zhou et al, 2018;Cai et al, 2020;Hu et al, 2020). Taylor and McLennan (1985).…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…The HMAs that have arc-like geochemical affinities in an intra-continental setting might be attributed to the inheritance of a previous subduction event in a metasomatized mantle source (Gao et al 2004;Gan et al 2020). Many similar cases can be found in a number of orogenic belts in western China, such as the upper Plioceneupper Pleistocene volcanic rocks in Tengchong (Zhao & Chen, 1992), the Permian basalt in the Santanghu basin in Xinjiang (Zhou et al 2006), the lower Permian volcanic rocks in the Western Junggar (Li et al 2016) and the Lower Carboniferous volcanic rocks in Inner Mongolia (Zhou et al 2018). Since the HNX Ocean in the Dundunshan area was likely closed during late Middle Devonian time, we suggest that the Dundunshan HMAs were formed in a post-collision extensional setting (Fig.…”
Section: C Tectonic Evolution Of Devonian Beishan Orogenmentioning
confidence: 92%